What Should Dnos Foster? a Single Dg or Multiple Small Dgs?: A Statistical Power-Flow Analysis for the Chilean Case - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2022)
Although distributed generation (DG) has been continuously growing in importance in recent years, the number of DG projects in developing countries is still little.In Chile, for example, small DGs have three possibilities for interconnecting with the grid, (i) a small means of distributed generation (PMGD), which has its own connection point with the grid up to 9 MW, (ii) a net-billing project (NB), which is installed in the premises of a consumer, up to 300 kW, or (iii) self-consumption projects.In this paper, we run a statistical power-flow analysis to compare the integration of DGs by means of either NB or PMGD. The comparison focuses on the steady-state nodal-voltage magnitudes and line-current magnitudes in both cases with respect to their pre-defined operational limits.The study uses the IEEE 33-bus system and defines three load cases: a base case, a minimum-load case, and a maximum-load case. We show that the connection of NB projects results in more violations of the nodal-voltage-magnitude limits, while the PMGD results in more violations of the line-current-magnitude limits, plus it generates higher active and reactive power losses. © 2022 IEEE.